2022
DOI: 10.52589/bjmms-rbdlyevj
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance Characteristics and Firm Value of Deposit Money Banks in Nigeria

Abstract: The degree of corporate and market procedures, lack transparency, distortions and poor corporate practices which results in corporate failures and abysmal corporate financial performance negatively influence corporate objectives. Hence, this study investigated the effects of corporate governance mechanisms on the value of deposit money banks in Nigeria from 2010 to 2020. The specific objectives include investigating the relationship between board size and Tobin q; evaluating the relationship between board inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Specifically, board independence, earnings persistence, and earnings predictability were found to have a positive significant effect on market capitalization, while gender diversity also exerted positive effect but was not statistically significant. The Fstatistics showed that the combined explanatory variables of board independence, gender diversity, earnings persistence, and earnings predictability had a positive effect on market capitalization, which is consistent with the findings of the studies by Tiep Le and Nguyen (2022), Ebimobowei (2022), Marie et al (2021), Boshnak (2021), Khanifah et al (2020), Ali et al (2020), andOchego et al (2019) who reported similar positive effects of corporate governance of firm's value and performance. However, the results of this study were insistent with the report of Aguguom et al (2019), which found a positive but insignificant effect of board independence on firm value.…”
Section: Interpretations 411 Pre-estimation Resultssupporting
confidence: 88%
“…Specifically, board independence, earnings persistence, and earnings predictability were found to have a positive significant effect on market capitalization, while gender diversity also exerted positive effect but was not statistically significant. The Fstatistics showed that the combined explanatory variables of board independence, gender diversity, earnings persistence, and earnings predictability had a positive effect on market capitalization, which is consistent with the findings of the studies by Tiep Le and Nguyen (2022), Ebimobowei (2022), Marie et al (2021), Boshnak (2021), Khanifah et al (2020), Ali et al (2020), andOchego et al (2019) who reported similar positive effects of corporate governance of firm's value and performance. However, the results of this study were insistent with the report of Aguguom et al (2019), which found a positive but insignificant effect of board independence on firm value.…”
Section: Interpretations 411 Pre-estimation Resultssupporting
confidence: 88%
“…Hasibuan and Khomsiyah (2019) state that corporate governance describes the means by which all stakeholders interested in the growth of the organisation attempt to ensure that managers take actions or implement mechanisms that protect the interests of the stakeholders. Appah (2022b) notes that such measures are required by the separation of ownership from management, an increasingly important attribute of contemporary organisation. The major aim of good corporate governance is to ensure the efficient use of resources to reduce corporate fraud and mismanagement in order to maximize and align the conflicting interests of all stakeholders (Yimbila, 2017).…”
Section: Mechanismsmentioning
confidence: 99%